2020
DOI: 10.1080/15564886.2020.1828210
|View full text |Cite
|
Sign up to set email alerts
|

Women Providing and Men Free Riding: Work, Visits and Gender Roles in Mexican Prisons

Abstract: Facing the Covid-19 pandemic, prisons in Mexico City prohibited visits. This sparked clearly gendered protests: male prison inmates complained that the restrictions left them without resources to deal with prison shortages, while women complained that it prevented them from sending resources to their families. Based on data from life story interviews conducted before the pandemic, we explore visits, prison work, and gendered child-rearing practices in Mexican prisons. We argue that incarcerated mothers adopt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Note how Semiri had to pay for her own necessities and was expected to provide for her family outside of prison (Agoff, Sandberg, and Fondevila 2020). This challenge is unique among the three studies but appears to be common among incarcerated people in Latin American-a challenge to incarcerated women that has largely been ignored by the English-language literature on incarcerated women.…”
Section: B Three Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Note how Semiri had to pay for her own necessities and was expected to provide for her family outside of prison (Agoff, Sandberg, and Fondevila 2020). This challenge is unique among the three studies but appears to be common among incarcerated people in Latin American-a challenge to incarcerated women that has largely been ignored by the English-language literature on incarcerated women.…”
Section: B Three Studiesmentioning
confidence: 99%
“…Prisons had an informal economy. By choice or because it was the only work available, women took part in informal arrangements such as setting up food stands or doing chores for wealthier prisoners (Agoff, Sandberg, and Fondevila 2020). Ximena, for example, after having worked in the formal industries, concluded that "I will not kill myself for just 80 pesos a day."…”
Section: B Three Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, there is a growing body of criminological research that studies the effects of the pandemic and the various restrictions imposed in the region on, for example, changes in crime pattens in Mexico City during the pandemic, such as crimes associated with public transport [8], burglary, vehicle theft [9], violence against women [37] and homicides [7]. There are also studies on problems related to prisons and the difficulties faced by various Latin American governments to resolve these [38,39]. It is possible that the issue of shootings has not yet been systematically dealt with due to the lack of empirical data or the challenge of accessing such data in the region.…”
Section: Crime During the Pandemicmentioning
confidence: 99%